Environmental Democracy: Extractive Industry in Mozambique and Possibilities for Ecological Modernization (Global Journal of Human-Social Science, 2025)
The article Environmental Democracy Extractive Industry in Mozambique and Possibilities for Ecological Modernization examines the dynamics between the expansion of Mozambique s extractive industry the resulting environmental and social impacts and the challenges of implementing environmental democracy in the country The study s main objective is to explore how environmental democracy can be integrated into natural resource governance promoting a more equitable transparent and participatory management model The research follows a qualitative approach based on literature review and documentary analysis of legislation institutional reports and case studies The main findings show that although Mozambique has a relatively advanced legal framework the practical implementation of mechanisms for public participation transparency and environmental justice remains weak and inconsistent Cases such as Nagonha highlight serious shortcomings in monitoring compensation and inclusion of affected communities Furthermore the extractive industry while significantly contributing to GDP has been characterized by uneven benefit distribution marginalization of local populations and environmental degradation The Study proposes ecological modernization as a potential path to reconcile economic growth with sustainability through the adoption of clean technologies institutional reforms and the strengthening of civil society It concludes that achieving environmental democracy in Mozambique requires not only legal reforms but also political will technical capacity and inclusive governance that values citizen participation in decision-making
Keywords: environmental democracy; extractive industry; public participation; ecological modernization